Mitochondrial uncoupling and lifespan - Mookerjee, Shona A. (2010)
The quest to understand why we age has given rise to numerous lines of investigation that have gradually converged to include metabolic control by mitochondrial activity as a major player. That is, the ideal balance between nutrient uptake, its transduction into usable energy, and the mitigation of damaging byproducts can be regulated by mitochondrial respiration and output (ATP, reactive oxygen species (ROS), and heat). Mitochondrial inefficiency through proton leak, which uncouples substrate oxidation from ADP phosphorylation, can comprise as much as 30% of the basal metabolic rate. This uncoupling is hypothesized to protect cells from conditions that favor ROS production. Uncoupling can also occur through pharmacological induction of proton leak and activity of the uncoupling proteins. Mitochondrial uncoupling is implicated in lifespan extension through its effects on metabolic rate and ROS production. However, evidence to date does not suggest a consistent role for uncoupling in lifespan. The purpose of this review is to discuss recent work examining how mitochondrial uncoupling impacts lifespan.